Pregled telekomunikacija u svijetu (stanje 31. 12. 1989.) - Zvonimir Jakobčić (Promet (Zagreb), 2012)
Telecommunications facilities have since their inception reported being on a steady increase all over the world. This paper while reviewing the status in 57 nations with highest number of main telephone connections furnishes the information on their capacities, density per 100 inhabitants and increase viewed at an average annual rate over the period of 1969-1989 and 1979-1989. Comparisons regarding the gross national product of individual countries have been drawn. The countries included in this review possess over 97% of world telephone capacities.